Widespread co-occurrence of two distantly related mitochondrial genomes in individuals of the leaf beetle Gonioctena intermedia. (8th November 2017) - Kastally, Chedly; Mardulyn, Patrick
Abstract : Mitochondrial genome heteroplasmy—the presence of more than one genomic variant in individuals—is considered only occasional in animals, and most often involves molecules differing only by a few recent mutations. Thanks to new sequencing technologies, a large number of DNA fragments from a single individual can now be sequenced and visualized separately, allowing new insights into intra-individual mitochondrial genome variation. Here, we report evidence from both (i) massive parallel sequencing (MPS) of genomic extracts and (ii) Sanger sequencing of PCR products, for the widespread co-occurrence of two distantly related (greater than 1% nucleotide divergence, excluding the control region) mitochondrial genomes in individuals of a natural population of the leaf beetle Gonioctena intermedia . Sanger sequencing of PCR products using universal primers previously failed to identify heteroplasmy in this population. Its occurrence was detected with MPS data and may have important implications for evolutionary studies. It suggests the need to re-evaluate, using MPS techniques, the proportion of animal species displaying heteroplasmy.